Reinforcement clipping over energy-sealed arteries: a technical caution - Talwar, Rajnish; Garg, Akhil; Basude, Ajay; Kumawat, Arvind (International Surgery Journal, 2025)
Energy-based vessel sealing is a trusted technique in modern surgery. However, the application of mechanical clips over a thermally sealed vessel can paradoxically disrupt the integrity of the seal. A 55-year-old male underwent radical surgery for a retromolar trigone malignancy. The facial artery was sealed with LigaSure and secondarily clipped. On postoperative day four, torrential bleeding from the stump led to a cardiac arrest. Re-exploration revealed that the clip had transected the energy-sealed segment. Reinforcement clipping over energy-sealed stumps may compromise vessel integrity. If additional control is needed, clips should be applied before sealing, not after. This case highlights the need for adherence to energy device principles and avoidance of reinforcement clipping over thermally sealed vessels.